Comparison of Malta HF Radar Currents with CMEMS Mediterranean MFC Data - Kozyrakis, Georgios V.; Nikolaidis, Andreas; Gauci, Adam; Zodiatis , George; Azzopardi, Joel; Galanis, George; Zammit, Audrey; D’Amico, Sebastiano; Alexandrakis, George; Metheniti, Vassiliki; Parasyris, Antonios; Kampanis , Nikolaos A. (Technical Annals, 2024)
This study evaluates hourly sea surface currents from the CALYPSO HF radar system against Copernicus CMEMS Med MFC data, covering the period from August 2022 to August 2023. The HF radar network, comprising fou sites in Malta and three in Sicily, provides high-resolution, real-time surface current data. Results show that HF radar currents display greater temporal and spatia variability than the CMEMS data, primarily due to differences in spatial-temporal resolution. Notably, extreme current velocities differ between the datasets, with both indicating high values influenced by regional bathymetry. While HF radar data reflect currents at the very surface layer, CMEMS data correspond to a depth of 1.5 m. Nevertheless, after detrending and outlier removal, HF radar data alig well with CMEMS Med MFC, especially in current direction. Both datasets depict a general anticyclonic circulation between northern Malta and southern Sicily. Periodic intensifications occur along the anticyclone's northern and southern edges. HF radar shows southeastward flow along Sicily’s southern coast and opposing currents near Malta's northern coast. In contrast, CMEMS data indicate stronger southeast flow along southern Sicily and generally weaker currents near Malta.